Stress-dependent scaling behavior of sub-coercive field dynamic hysteresis in Pb(Zr1/2Ti1/2)O3-Pb(Zn1/3Nb 2/3)O3 ceramic systems - N. Wongdamnern (2018)
Stress dependence and scaling behavior of sub-coercive field dynamic ferroelectric hysteresis were investigated in (1-x)PZT-(x)PZN bulk ceramics, where x = 0.1, 0.2, 0.3, 0.4, and 0.5. The results shown that hysteresis area < A >, remnant polarization (Pr), and coercive field (EC) increase with increasing of field amplitude (E0), while decrease with increasing of frequency and compressive stress similar to previous investigations in bulk ceramics. The scaling relations of hysteresis area < A > against frequency f, field amplitude E0, and stress σ for the minor loops took a form of < A-Aσ = 0> α fα E0β σγ with range of (-0.42) to (-0.34), (3.32) to (4.03), and (0.19) to (0.38) for exponents α, β, and γ, respectively, depending on compositions, which are very similar to that of soft and hard PZT bulk ceramics. This study suggests that the domain structures play a key role in controlling dynamic hysteresis behavior of ferroelectric materials. Copyright © Taylor & Francis Group, LLC.